Exposição das crianças ao fumo ambiental do tabaco (FAT): avaliação de uma intervenção preventiva - Precioso, J (2012)
To evaluate the effectiveness of the preventative programme "Smoke-free Homes" undertaken in 4th year children and their parents or guardians, aiming to reduce children's exposure to second hand smoke (SHS) in the home. MATERIAL AND METHODS: This was a pre- and post-test pre-experimental study, in students from 32 Braga district primary schools 2007/08. A self-administered and structured questionnaire was given out to 795 students in the classroom before and after the programme. In analysing data, we used the chi-squared test for the categorical variables. RESULTS: The rate of children exposed to regular or occasional SHS due to living with at least one smoker dropped from 42.2% to 32.6% (p=0.001). The percentage of students, children of smokers who stated that their father smoked regularly or occasionally at home, dropped from 68.0% pre-test to 51.6% posttest (p=0.000). No significant reduction was seen in mothers. CONCLUSION: Based on the data, we can conclude that the "Smoke-free Homes" programme was effective in preventing smoking in the home, and therefore reducing the rate of children exposed to SHS by about 10%. However, it appears that about a third of children are still exposed, which highlights the need for further measures in this area. Healthcare professionals, particularly those working in Paediatrics, should advise parents to quit smoking, especially in the home.